2020
DOI: 10.3390/pharmaceutics12111129
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of 1α,25-Dihydroxyvitamin D3 on the Expressions and Functions of Hepatic CYP and UGT Enzymes and Its Pharmacokinetic Consequences In Vivo

Abstract: The compound 1α,25-Dihydroxyvitamin D3 (1,25(OH)2D3) is the active form of vitamin D3 and a representative ligand of the vitamin D receptor (VDR). Previous studies have described the impacts of 1,25(OH)2D3 on a small number of cytochrome P450 (CYP) and uridine diphosphate-glucuronyltransferase (UGT) enzymes, but comparatively little is known about interactions between several important CYP and UGT isoforms and 1,25(OH)2D3 in vitro and/or in vivo. Thus, we investigated the effects of 1,25(OH)2D3 on the gene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…The metabolic stability of SFN and SFN-NAC was evaluated in human and rat liver microsomes as previously reported [ 23 ], with minor modifications. Briefly, test compounds (1 μM) were incubated with rat and human liver microsomes (final concentration 1 mg/mL protein) containing 1 mM NADPH.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic stability of SFN and SFN-NAC was evaluated in human and rat liver microsomes as previously reported [ 23 ], with minor modifications. Briefly, test compounds (1 μM) were incubated with rat and human liver microsomes (final concentration 1 mg/mL protein) containing 1 mM NADPH.…”
Section: Methodsmentioning
confidence: 99%
“…For example, 1,25(OH) 2 D 3 administration results in a decrease in rat kidney organic anion transporters (rOAT1/OAT3) expression, leading to a dramatic decrease in renal clearance of cefadroxil and cefdinir (Kim et al 2014). Our recent study also demonstrated that 1,25(OH) 2 D 3 downregulates the mRNA and protein expression of Cyp2b1 and Cyp2c11 in rats, which consequently alters the metabolic function and systemic pharmacokinetics of bupropion and tolbutamide (substrates of Cyp2b1 and Cyp2c11, respectively) (Doan et al 2020). In another recent study of our group, 1,25(OH) 2 D 3 regulated the expression of rat organic cation transporters (rOCT) and rat multidrug and toxin extrusion proteins (rMATE), which was evidenced by a decrease in renal and non-renal (metabolic) clearance of procainamide hydrochloride (an organic cation transporter substrate) and a decrease in the renal clearance of the metabolite N-acetyl procainamide (Balla et al 2021).…”
Section: Introductionmentioning
confidence: 77%
“…Male Sprague Dawley rats (7-8 weeks old, 220-280 g; Nara Bio Tech., South Korea) were acclimated to laboratory conditions and provided ad libitum access to food and water and maintained under 12-h/12-h light/dark cycles for one week. The treatment of 1,25(OH) 2 D 3 (2.56 nmol/kg/day) was performed as previously reported (Chow et al 2009(Chow et al , 2010Maeng et al 2011;Doan et al 2020;Balla et al 2021). Rats were randomly divided into the control and 1,25(OH) 2 D 3treated groups.…”
Section: 25(oh) 2 D 3 Pretreatment In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1α,25-dihydroxyvitamin D3 did not inhibit the metabolic activity of bupropion and tobutamide in rat liver microsomes, the decreased metabolic intrinsic clearance of bupropion and tobutamide could be associated with the decreased Cyp2b and Cyp2C expressions. However, the in vitro effect of 1α,25-dihydroxyvitamin D3 on Cyp2b and Cyp2C does not directly translate into the pharmacokinetics of bupropion and tobutamide and their metabolites hydroxybupropion and hydroxytobutamide because of the complicated regulation of 1α,25-dihydroxyvitamin D3 on renal function, protein binding, and other transport activities [ 7 ]. A lack of in vitro and in vivo correlation was also reported by Neag et al [ 8 ].…”
mentioning
confidence: 99%